The role of Cu1–O3 species in single-atom Cu/ZrO2 catalyst for CO2 hydrogenation - Zhao, Huibo; Yu, Ruofan; Ma, Sicong; Xu, Kaizhuang; Chen, Yang; Jiang, Kun; Fang, Yuan; Zhu, Caixia; Liu, Xiaochen; Tang, Yu; Wu, Lizhi; Wu, Yingquan; et al. (Nature catalysis, 2022)
Copper-based catalysts for the hydrogenation of CO2 to methanol have attracted much interest. The complex nature of these catalysts, however, renders the elucidation of their structure–activity properties difficult. Here we report a copper-based catalyst with isolated active copper sites for the hydrogenation of CO2 to methanol. It is revealed that the single-atom Cu–Zr catalyst with Cu1–O3 units contributes solely to methanol synthesis around 180 °C, while the presence of small copper clusters or nanoparticles with Cu–Cu structural patterns are responsible for forming the CO by-product. Furthermore, the gradual migration of Cu1–O3 units with a quasiplanar structure to the catalyst surface is observed during the catalytic process and accelerates CO2 hydrogenation. The highly active, isolated copper sites and the distinguishable structural pattern identified here extend the horizon of single-atom catalysts for applications in thermal catalytic CO2 hydrogenation and could guide the further design of high-performance copper-based catalysts to meet industrial demand.Copper-based catalysts are traditionally very effective for the hydrogenation of CO2 to methanol, although control over the active site has remained elusive. Here, the authors design a Cu1/ZrO2 single-atom catalyst featuring a Cu1–O3 site responsible for a remarkable performance at 180 °C.